"I love the cute caterpillar!" autistic children's production of internal state language across contexts and relations to Joint Attention and theory of mind. (April 2015) - Kristen, Susanne; Vuori, Maria; Sodian, Beate
Highlights: First study to explore autistic children's internal state language across different contexts as an indicator of their psychological comprehension. Results revealed that deficits in autistic children's internal state language were highly specific and varied by context. Only cognitive internal state talk in a context requiring joint attention skills was indicative of autistic children's advanced psychological comprehension. Implications of this research for diagnosis and therapy of socio-communicative deficits in autism are discussed. Abstract: Research on internal state language in autistic children reveals an uneven pattern. While some studies show that high-ability autistic children are impaired across a broad range of internal state term categories (e.g., desires, emotions and cognitive terms), other research shows that autistic children are more selectively impaired in their talk about cognitive states. Finally, some studies even demonstrate no impairments. The different findings have largely been explained by context effects. However, to date, studies have yet to compare the same children across different contexts to corroborate this interpretation. Further, studies involving contexts where autistic children's reactivity is actively triggered by providing clear joint attention cues or by exploiting autistic children's intense interest in objects are lacking. Thus, this study tested internal state language from different categories across three different contexts (narrative context, motivating mechanical toy context, elicited interactive joint attention context) and related it to joint attention skills and children's theory of mind. Results revealed that deficits in autistic children's internal state language were highly specific and relation to theory of mind varied by context. In sum, this research suggests that both theorists and practitioners need to take into account context when studying or promoting autistic individuals' psychological comprehension.